Environmental bacterial and fungal contamination in high touch surfaces and indoor air of a paediatric intensive care unit in Maputo Central Hospital, Mozambique in 2018. Issue 4 (December 2022) - Maphossa, Vânia; Langa, José Carlos; Simbine, Samuel; Maússe, Fabião Edmundo; Kenga, Darlene; Relvas, Ventura; Chicamba, Valéria; Manjate, Alice; Sacarlal, Jahit
Summary: Background: The hospital environment serves as a reservoir of microorganisms which may be associated with healthcare-associated infections (HCAI). The study of environmental contamination with microorganisms is a method for the assessment of hospital environmental hygiene. We sought to evaluate the environmental colonisation of a national reference hospital unit, using the total aerobic colony count (ACC) and the isolated microorganisms, as assessment tools. Methods: A cross-sectional study was conducted in the Paediatric Intensive Care Unit (PICU) of the Hospital Central de Maputo during a four-week period in 2018. Surfaces and air were sampled before and after room cleaning, using swabs and passive air method. Those samples were processed at the microbiology laboratory where total ACC levels were evaluated, and microorganisms were isolated, identified and assessed for antibiotic susceptibility. Discussion: Comparison of the total median ACC of the indoor air (287 cfu/m 3 before and 195 cfu/m 3 after) and surfaces (0.38 cfu/cm 2 before and 0.33 cfu/cm 2 after) before and after room cleaning did not show significant differences ( P >0.05). Microorganisms of epidemiological importance, including coagulase negative staphylococci (CoNS), Klebsiella pneumoniae and Serratia odorifera were isolated and all of these three were multi-drug resistant (MDR). Conclusion: The results showed controlled contamination levels on high touch surfaces in the patient environment and a high level of contamination of the indoor air suggesting deficiencies in the PICU environmental decontamination process. There was evidence of the presence of fungi and MDR species of epidemiological importance in the context of HCAI.